OP0186 5-Year Organ Damage Accrual and Safety in Patients with Sle Treated with Belimumab Plus Standard of Care. (9th June 2015) - Bruce, I.N.; Urowitz, M.; van Vollenhoven, R.; Aranow, C.; Fettiplace, J.; Oldham, M.; Menius, E.; Wilson, B.; Molta, C.; Roth, D.; Gordon, D.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic relapsing and remitting condition in which long-term damage can accrue over time. Objectives: To examine long-term organ damage and safety following 5 years of treatment with belimumab plus standard of care (SoC) in patients with SLE. Methods: We examined pooled interim data (GSK201223) from two open-label studies that enrolled patients who completed the BLISS-52 and BLISS-76 studies. Patients received belimumab plus SoC every 4 weeks. Baseline was defined as prior to the first dose of belimumab. SLICC Damage Index (SDI) values were assessed every 48 weeks (yearly interval). Results: 998 patients comprised the modified intent-to-treat population at baseline: 940 (94.2%) were female, with a mean (SD) age of 38.7 (11.49) years and disease duration of 6.69 (6.24) years. The mean (SD) SELENA-SLEDAI and SDI were 8.2 (4.18) and 0.7 (1.19), respectively. Reasons for study withdrawal included: subject request (16.8%), AEs (8.5%), other (7.0%), and investigator decision (4.8%). 411 (41.2%) patients had damage at baseline (SDI =1: 235 [23.5%]; SDI ≥2: 176 [17.6%]). At Years 5–6 (n=403), 343 (85.1%) patients had no change from baseline in SDI score (SDI +1: 46 [11.4%, SDI +2: 13 [3.2%], SDI +3: 1 [0.2%]). The mean (SD) change in SDI was +0.19 (0.481). Of patients with damage at baseline, 132/162 (81.5%) had no change in SDI (SDI +1: 22/162 [13.6%], SDI +2: 8/162 [4.9%], SDI +3: 0/162 [0%]), mean (SD) change in SDI was +0.23 (0.529). Of patients without baseline damage, 211/241 (87.6%) had no change in SDI (SDI +1: 24/241 [10.0%], SDI +2: 5/241 [2.1%], SDI +3: 1/241 [0.4%]), mean change (SD) in SDI was +0.15 (0.444). Overall, 433 (43.4%) of patients had a drug-related AE. The most common drug-related AEs were infections/infestations, 282 (28%) patients, and gastrointestinal disorders, 139 (14%) patients. 23 (2%) patients had an adjudicated opportunistic infection (OI); 4 (0.4%) patients had a serious OI. 87 (8.7%) patients had herpes zoster. 88 (8.8%) patients had an AE causing belimumab discontinuation. 11 deaths occurred during the study period; 2 deaths occurred after study exit. Conclusions: Patients with moderate to severe SLE treated with belimumab plus SoC for 5 years had a low incidence of organ damage accrual and clinically manageable rates of AEs. Importantly, patients with pre-existing organ damage at study entry experienced similar rates of damage accrual compared with those with no baseline damage. As existing damage is a known risk for future damage accrual, our data suggest that belimumab may have a positive effect on risk factors for future damage that requires further evaluation. Acknowledgements: Studies funded by GlaxoSmithKline (study #201223) and Human Genome Sciences. Louisa Pettinger, PhD, Fishawack Indicia Ltd, UK, assisted with the abstract submission and was funded by GSK. Disclosure of Interest: I. Bruce Grant/research support from: UCB, GSK, Roche, Sanofi, Consultant for: UCB, Eli Lilly, GSK, Medimmune, Pfizer, Employee of: University of Manchester, Speakers bureau: UCB, GSK, Medimmune, M. Urowitz Grant/research support from: GSK, UCB, Eli Lilly, Consultant for: GSK, UCB, Eli Lilly, R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, Pfizer, Roche, UCB, Consultant for: AbbVie, Biotest, BMS, Crescendo, Eli Lilly, GSK, Janssen, Merck, Pfizer, Roche, UCB, Vertex, C. Aranow Grant/research support from: GSK, UCB, Eli Lilly, Celgene, Janssen, Consultant for: GSK, UCB, Eli Lilly, Celgene, Janssen, J. Fettiplace Shareholder of: GSK, Employee of: GSK, M. Oldham Shareholder of: GSK, Employee of: GSK, E. Menius Shareholder of: GSK, Employee of: GSK, B. Wilson Shareholder of: GSK, Employee of: GSK, C. Molta Shareholder of: GSK, Employee of: GSK, D. Roth Shareholder of: GSK, Employee of: GSK, D. Gordon Shareholder of: GSK, Employee of: GSK